Functional and radiological outcome of locking plate in displaced fracture of distal end radius - Bidary, Suraj; Pandey, Suresh; Gupta, Hemant Kumar; Das, Manoj; Aryal, Roshani; Ghimire, Pradeep; Bhattarai, Kushal (Journal of Chitwan Medical College, 2021)
Background: Distal radius fracture is the most common fracture of upper extremity. There are wide variety of treatment options including plaster, ligamentotaxis, percutaneous pinning and plating for the treatment of displaced distal end radius fracture in the adult. Each option has got its own pros and cons. This study was designed with an objective of assessment of functional and radiological outcome of displaced distal end radius fracture treated with volar locking plate. Methods: This was a retrospective study of closed displaced fracture of distal end radius managed with volar locking plate from January 2018 to September 2020. Data were collected from the case chart and included patient’s demography, fracture characteristics, radiological parameters, range of motion and complications. Data analysis was done using Statistical package for social science 20.0 software. Descriptive statistics for categorical variable was used and mean of the continuous data was compared using student’s t-test. P-value <0.05 was considered as statistically significant. Results: The mean age of patient was 35.87 years after analysis of total of 30 patients with mean follow up of 12.87 months. Road traffic accident (76.7%) was the most common mode of injury. There were 36.7% Association of Osteosynthesis (AO) type B and C injuries, each. The mean Quick Disabilities of Arm, Shoulder and Hand (DASH) score was 1.13 (range 0 - 6.81) at the final follow up. The mean union time of the fracture was 6.6 weeks. One patient had stiffness and one developed reflex sympathetic dystrophy. Conclusions: Functional and radiological outcome of the displaced distal end radius in adult treated with open reduction and internal fixation with locking plate was found good to excellent in most of the cases.